The effect of technique and ability on the VO2-heart rate relationship in rock climbing - Fryer, S.; Dickson, T.; Draper, N.; Eltom, M.; Stoner, L.; Blackwell, G. (Sports Technology, 2012)
Previous studies have speculated that the disproportionate rise in heart rate for a given VO2 may be due to anxiety, increased time spent in isometric contraction and the possible presence of the metaboreflex. The current study measured time spent in isometric contraction, rest time, pre-climb anxiety, heart rate and VO2 responses in advanced (n = 11) and intermediate (n = 11) rock climbers performing at or near their maximum self-reported on-sight grade (19/22 Ewbank). Results showed a non-significant difference (p>0.05) between groups for climb time, pre-climb heart rate and state anxiety. Throughout the majority of the climbs, it was observed that the intermediate group's heart rate per VO2 ratio was significantly greater (p < 0.05) than that seen in the advanced group. Advanced climbers spent a significantly greater period of time (p < 0.05) in an isometric position but interestingly spent a significantly greater period of time (p < 0.05) shaking out and actively resting the arms. It would appear that pre-climb anxiety played no part in the disproportionate rise in heart rate per VO2. However, the significantly increased rest time (p < 0.05) and the ability to make tactical route decisions may have increased recovery forearm blood flow, reducing metabolites and the presence of the metaboreflex.